SELF–ACTUALIZATION OF HUMAN’S NEEDS: THE PORTRAIT OF A WOMAN’S STRUGGLE AGAINST PATRIARCHY IN NH. DINI’S NOVEL BANDUNGAN STREET (Language Circle: Journal of Language and Literature, 2010)
Patriarchy places Mur, the main character in NH Diniâ€™ s novel entitled â€œBandungan Streetâ€, as the secondary citizen, since its orientation is men. This condition impedes her to reach Maslowâ€™s hierarchy of needs. The apathy and sadness come since those needs cannot be met. It prompted her to be powerless. Then, she uses the â€˜Will to Powerâ€ proposed by Nietzsche as to control the undesired condition to empower herself. At last, she can achieve self-actualization, to be the best she can be, as the highest needâ€™s rank. It proves that women can even be the better species if they are also given the same opportunity. Â  Key words: patriarchy, will to power, self-actualization.